Through-Wall Image Enhancement Using Fuzzy and QR Decomposition - Muhammad Mohsin Riaz; Abdul Ghafoor (The Scientific World Journal, 2014)
QR decomposition and fuzzy logic based scheme is proposed for through-wall image enhancement. QR decomposition is less complex compared to singular value decomposition. Fuzzy inference engine assigns weights to different overlapping subspaces. Quantitative measures and visual inspection are used to analyze existing and proposed techniques.